Pengaruh Era Modern Terhadap Dunia Bisnis - Khalisya Nurul Sadrina; M Rifa Fadullah J; Niwani Sitorus; Nuraini Sukma Nafira; Jihan Zalfa Syabannia; Keyla Fatima Zahra; Irfan Wahyu Pratama; Muhammad Fathul Azmi; Sutiawati Sutiawati; Elyzer Julia Rohmah; Faris Barianto; Moh. Okka Meiherdian (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the impact of the modern era on the business world, with a focus on digital transformation and its impact on business management and human resources. Through qualitative analysis based on literature review and digital data analysis, this study explores how technological advancements have revolutionized business operations, organizational culture, and workforce development. The findings suggest that digital technology has fundamentally changed the business paradigm, requiring organizations to adapt through digital skills development, technology integration, and cultural transformation. Organizations must invest in continuous training to address skills gaps and improve productivity in the digital era. This study contributes to the understanding of how businesses can effectively navigate and thrive in the modern digital era.